Teaching human development for educators - Smith, M. Cecil; Fong, Carlton; Carney, Russell N., 1950- (Theory to practice: educational psychology for teachers and teaching, 2024)
"In an age where the quality of teacher education programs has never been more important, educators need a fundamental understanding of human growth, development, and change at different ages and stages across the life span. The present volume draws upon the latest research to help teacher preparation instructors select and convey essential content on human development. Such efforts serve to prepare education professionals to work with infants, children, adolescents, and adults across diverse educational settings. The chapters included in this volume summarize empirical research that supports the teaching of human development as it applies to PreK-12 and postsecondary settings, describe instructional practices used in college courses that are effective for teaching teachers-in-training about human development, and provide a systematic discussion of issues that influence the teaching of human development theories, research, and classroom applications. The contributing authors are accomplished educational and developmental psychologists that have years of experience in teacher preparation. Their respective chapters provide insights into the challenges that teachers-in-training confront in learning about human growth and development and how novice teachers can apply knowledge of human development in their professional practice"--